UNIT 7.17 The Ussing Chamber Assay to Study Drug Metabolism and Transport in the Human Intestine. Issue 1 (22nd June 2017) - Kisser, Beatrice; Mangelsen, Eva; Wingolf, Caroline; Partecke, Lars Ivo; Heidecke, Claus‐Dieter; Tannergren, Christer; Oswald, Stefan; Keiser, Markus
Abstract : The Ussing chamber is an old but still powerful technique originally designed to study the vectorial transport of ions through frog skin. This technique is also used to investigate the transport of chemical agents through the intestinal barrier as well as drug metabolism in enterocytes, both of which are key determinants for the bioavailability of orally administered drugs. More contemporary model systems, such as Caco‐2 cell monolayers or stably transfected cells, are more limited in their use compared to the Ussing chamber because of differences in expression rates of transporter proteins and/or metabolizing enzymes. While there are limitations to the Ussing chamber assay, the use of human intestinal tissue remains the best laboratory test for characterizing the transport and metabolism of compounds following oral administration. Detailed in this unit is a step‐by‐step protocol for preparing human intestinal tissue, for designing Ussing chamber experiments, and for analyzing and interpreting the findings. © 2017 by John Wiley & Sons, Inc.